Estado da arte: educação fiscal na base da dados da CAPES - de Oliveira, Edilene Maria; Fernandez, Talita Andréia (Revista Vozes dos Vales: Publicações Acadêmicas, 2021)
Tax education is not simply about explaining what taxes are and the reason they should be paid, nor is it a strategy to raise more money. It exists, mainly, so that we citizens come to understand the social value of taxes and with that the resumption of citizen participation in the exercise of active, responsible and shared citizenship. This paper presents the survey of state of the art on the subject of Tax Education in the scientific universe. It aimed to map the existing scientific / academic productions, from 2013 to 2019, in Brazil. Focusing on theses and dissertations, using the catalog of theses and dissertations from the Coordination for the Improvement of Higher Education Personnel (CAPES) as a search platform. The methodology consisted of bibliographic research with an approach to quantitative data and analysis of the works which were found. Based on the mapping of published scientific productions, scientific visibility and dissemination are aimed at, thus promoting access to research and the deepening of this area of knowledge, serving all members of the academic community from different areas of knowledge, they may be undergraduate or graduate students, as well as teaching researchers and supervisors. We can observe that despite being a topic of relevance for the present time, little has been discussed in academia, that is worthy of a reconsideration and a deeper look at the dissemination of the subject under study.